2021
DOI: 10.1039/d1md00110h
|View full text |Cite|
|
Sign up to set email alerts
|

Truncated S-MGBs: towards a parasite-specific and low aggregation chemotype

Abstract: This paper describes the design and synthesis of Strathclyde minor groove binders (S-MGBs) that have been truncated by the removal of a pyrrole ring in order to mimic the structure of the natural product, disgocidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The N -oxide S-MGBs, interestingly, were not found to be active against Staphylococcus aureus , in contrast to their precursors, which include some of the most active S-MGBs against Gram-positive bacteria. In another study in which the structures of S-MGB-1 , S-MGB-2 and S-MGB-3 were truncated by the removal of one pyrrole from the structure, a reduction in Gram-positive activity was also observed [ 19 ]. In other studies, antifungal activity was not found for the N -oxides either (data not reported).…”
Section: Resultsmentioning
confidence: 99%
“…The N -oxide S-MGBs, interestingly, were not found to be active against Staphylococcus aureus , in contrast to their precursors, which include some of the most active S-MGBs against Gram-positive bacteria. In another study in which the structures of S-MGB-1 , S-MGB-2 and S-MGB-3 were truncated by the removal of one pyrrole from the structure, a reduction in Gram-positive activity was also observed [ 19 ]. In other studies, antifungal activity was not found for the N -oxides either (data not reported).…”
Section: Resultsmentioning
confidence: 99%
“…MGB-BP-3 and S-MGB-245 were prepared as previously described in refs ( 4 ) and ( 11 ), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Their favorable cytotoxicity profiles to mammalian cells give them selectivity indices that make them suitable for development as novel drugs. This has enabled extensive in vitro and several in vivo experiments to provide proof of concept for S-MGBs as a novel class of anti-infective agent against bacterial, fungal, viral, and parasitic infections. One of these compounds, MGB-BP-3 (Figure ) has successfully completed Phase IIa clinical trials for the treatment of Clostridioides difficile associated disease (NCT03824795). MGB-BP-3 also has potent (<1 μg/mL) antibacterial activity against methicillin-resistant and methicillin-susceptible Staphylococcus spp., Streptococcus spp., and vancomycin-resistant and vancomycin-susceptible Enterococcus spp .…”
mentioning
confidence: 99%